1994
DOI: 10.1099/0022-1317-75-5-1149
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Broad Spectrum PCR Assay for Papillomaviruses and its Application in Screening Lung Cancer Biopsies

Abstract: A PCR assay was developed to detect known and as yet unidentified papillomaviruses (PVs). For this purpose we analysed the conserved amino acid sequences in the L1 and E1 open reading frames of 45 human and nine animal PVs. Candidate regions for the design of a primer were identified as those having the least number of amino acid and nucleotide sequence variants among the different PVs. These regions in the L10RF have been described previously. We modified the sequences of the backward and the forward primers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 23 publications
4
92
0
2
Order By: Relevance
“…However, reports concerning the HPV detection in lung tumours show several discrepancies. Several studies reported the presence of HPV-DNA within tumours with variable frequency (11)(12)(13)(14)(15)(16)(17)(18). HPV16 and 18 genotypes were the most frequently found in lung tumours.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports concerning the HPV detection in lung tumours show several discrepancies. Several studies reported the presence of HPV-DNA within tumours with variable frequency (11)(12)(13)(14)(15)(16)(17)(18). HPV16 and 18 genotypes were the most frequently found in lung tumours.…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 100 different PV genotypes have been identified, of which approximately 48 types have been detected in human cutaneous lesions (12). These include the beta-papillomavirus (beta-PV) genus comprising the human papillomavirus (HPV) types 5,8,9,12,14,15,17,19,20,21,22,23,24,25, 36, 37, 38, 47, 49, 75, 76, 80, and 93 and candidate types 92 (cand92) and cand96. Based on partial sequences, however, probably more than 35 new types have to be added to the 25 known beta-PV types (19).…”
mentioning
confidence: 99%
“…The rate of positivity varied between 4.2% and 31% (19)(20)(21), while in carcinomas with condylomatous changes the rate was higher (42%) (20). In contrast other investigators reported absence of HPV in lung cancer (37,38), this divergence may be due to the differences in the sensitivity and specificity of the methods applied, as well as to epidemio-logical factors. In the current study we confirm the presence of HPV in lung carcinomas, using primers from both the E6 and LI ORFs.…”
Section: Discussionmentioning
confidence: 45%